Inovasi Kurikulum Pai Berbasis Pembiasaan Pada Anak Usia 5-6 Tahun Di Raudhatul Athfal (RA) Azzahra Way Jepara Lampung Timur - yanti, Sefri; Sukiman, Sukiman (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2022)
Abstract: Understanding of Islamic religious education that must be given to children from an early age. This education will create children who believe, have good character and have good character. The research method uses descriptive qualitative research which explains the events as they are in accordance with the facts on the ground. The subjects of this study consisted of principals, teachers and students. The data analysis technique used data triangulation. Data collection techniques through observation, documentation and interviews. The research was carried out at RA Azzahra Way Jepara, East Lampung. The results showed that the PAI curriculum innovation development carried out at RA Azzahra Way Jepara, East Lampung could be carried out well and the children's abilities were able to develop significantly through habituation activities. The PAI development method is carried out in a planned manner according to a predetermined schedule of activities every week. Through habituation activities, children cultivate a religious attitude, good character, and akhlaqul karimah attitude